Combination of cassava starch biopolymer and essential oils for coating table eggs - Oliveira, Gabriel da Silva; McManus, Concepta; Pires, Paula Gabriela da Silva; dos Santos, Vinícius Machado (Frontiers in Sustainable Food Systems, 2022)
This work aimed to evaluate the eggshell microbiota and the internal egg quality after coatings with cassava starch biopolymer enriched with different essential oils during 35 days of storage at 20°C. A total of 369 brown table eggs were used and distributed in the following treatments: uncoated eggs, coated with cassava starch + Ginger essential oil (CS+GIN), cassava starch + Lemongrass essential oil (CS+LEM), and cassava starch + Tahiti lemon essential oil (CS+TAH). The count of total aerobic mesophilic bacteria on coated eggshells at 0 and 35 days of storage were similar to each other (mean 0.70 ± 0.37 and 0.91 ± 0.22 log10 CFU/mL) and significantly lower compared to uncoated eggs (2.21 ± 0.17 and 3.17 ± 0.22 log10 CFU/mL), in that order. On the 35th day, coated eggs showed similar Haugh unit (HU) values between them (mean 70.61 ± 5.35; classified as A - high quality) and significantly higher than uncoated eggs (51.60 ± 4.28; classified as B - average quality). Cassava starch coatings added with essential oils preserved the internal quality of the eggs during storage for 5 weeks at 20°C, reducing the eggshell microbiota and effectively keeping it at low levels during storage.